Influence of the HLA-DQB1*0201 allele on the immune response in a Schistosoma mansoni infection. - Reis, Eliana Almeida Gomes (2008)
Fundação Oswaldo Cruz. Centro de Pesquisa Gonçalo Moniz. Salvador, BA, Brasil